Jobbtilfredshet og livskvalitet blant norske hjemmesykepleiere - Liv Halvorsrud; Jelena Kuburović; Randi Andenæs (Septentrio Academic Publishing, 2017)
Job Satisfaction and Quality of Life among Norwegian Homecare Nurses: a cross-sectional study The aim of this cross-sectional study was to investigate job satisfaction and quality of life among homecare nurses. A questionnaire including socio demographic variables, the Job Satisfaction Scale and the World Health Organization Quality of Life measurement was used to assess data (N = 126, mean age 39 years, 78 percent were women). The study showed moderate overall job satisfaction among homecare nurses. Satisfaction with colleagues had the highest item score in job satisfaction. Moderate satisfaction was displayed for the following items; responsibility you are given, variation on work, your opportunities to use your skills, freedom to choose your own methods of working, your physical working conditions, your work hours, and recognition you get for good achievements. Overall quality of life as well as the domains; physical, psychological, social relations and environment, showed high scores. Job satisfaction was significantly associated with both physical and environment domain of quality of life.